Fundamentals of entrepreneurship (ENT300) : Enviroceria Sdn. Bhd. / Immanuel David ... [et al.] - David, Immanuel; Chundang, Cliff Howell; Tuah, Hasif Aiman; Azaman, Mohd.Amiruddin
Enviro Ceria Sdn. Bhd. is a private owned company that being run since 2010 that specializing in environmental, regulatory compliance consultations, permitting, safety and health, testing, energy management services and general works. This company was formed to help another organisation with their work such as environmental regulations. This company were supported by strong management team consist of professional, experience individuals and relevant technical people to help organisations to achieve compliance in environmental requirement.